Sobre o protagonismo laical do catolicismo popular: pistas para reflexão - Filho, José Reinaldo Felipe Martins (2018)
The present article is an attempt to rise some reflecting clues on the lay protagonism presents in the Brazilian popular Catholicism, aiming at overcoming a merely dichotomous reading and opposition between official and popular spheres. In this way, it is worth to recur to concepts already established by researches in Theology, Religion Science, as well as their interfaces with Antropology, Philosophy and Sociology. Among the main characteristics of popular Catholicism that point out in the direction of the lay Christian are communitarian dimention, capacity of identity espacio-temporal resignification and the absence of mediators such as saints, in the relationship between Heaven and Earth. The subject matter, whose contribution meets our current discussions about identity and lay Christians, is of great amplitude and still needs to be explored in depth.
Este artigo tenta suscitar algumas pistas de reflexão sobre o protagonismo laical presente no catolicismo popular brasileiro, tendo como mote superar uma leitura meramente dicotômica e de oposição entre as esferas do oficial e do popular. Vale-se, para isso, de conceitos já consolidados pelas pesquisas em Teologia e Ciências da Religião, bem como de suas interfaces com a Antropologia, a Filosofia e a Sociologia. Entre as principais características do catolicismo popular que apontam para o protagonismo dos leigos estão a dimensão comunitária, a capacidade de ressignificação espaçotemporal e identitária e a ausência de intermediadores na relação entre céu e terra, como é o caso dos santos. Trata-se de um vasto e rico horizonte a ser explorado, cuja contribuição também alcança nossas atuais discussões sobre a identidade dos cristãos leigos.
Keywords: Identidade; Catolicismo popular; Protagonismo laical; Identity; Popular Catholicism; Lay protagonism